2017
DOI: 10.1016/j.epsl.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Active tectonics of the Calabrian subduction revealed by new multi-beam bathymetric data and high-resolution seismic profiles in the Ionian Sea (Central Mediterranean)

Abstract: International audienceThe detailed morphology and internal structure of the Calabrian accretionary wedge and adjacent Eastern Sicily margin are imaged in unprecedented detail by a combined dataset of multi-beam bathymetry and high-resolution seismic profiles. The bathymetric data represent the results of 6 recent marine geophysical surveys since 2010 as well as a compilation of earlier surveys presented as a 2 arc-sec (60 m) grid. Several distinct morpho-tectonic provinces are identified including: the deeply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 49 publications
5
106
1
Order By: Relevance
“…A slab length offset between the originally attached Calabrian and the Kabylides slab might be at the origin of the initiation of a subduction-transform edge propagator (STEP, Govers & Wortel, 2005) fault that then separated these into two slabs ( van Hinsbergen, Mensink, et al, 2014). The modern-day fore-arc STEP fault is thought to be located either at the Alfeo Fault system (Dellong et al, 2018;Gutscher et al, 2016Gutscher et al, , 2017 or at the Ionian Fault system (Polonia et al, 2011;Scarfì et al, 2018) (Figure 2). An earlier proposition that the STEP fault follows the Malta Escarpment, a 3-km-high feature offshore E Sicily (Argnani & Bonazzi, 2005) formed during the Tethyan rifting history of the Ionian Sea (Frizon de Lamotte et al, 2011;Gallais et al, 2011), seems unlikely given the absence of tectonic deformation along the central to southern Malta Escarpment since the Messinian, on the basis of high-resolution seismic profiles shot across the escarpment (Gutscher et al, 2016).…”
Section: Tectonic History Of the Study Regionmentioning
confidence: 99%
See 3 more Smart Citations
“…A slab length offset between the originally attached Calabrian and the Kabylides slab might be at the origin of the initiation of a subduction-transform edge propagator (STEP, Govers & Wortel, 2005) fault that then separated these into two slabs ( van Hinsbergen, Mensink, et al, 2014). The modern-day fore-arc STEP fault is thought to be located either at the Alfeo Fault system (Dellong et al, 2018;Gutscher et al, 2016Gutscher et al, , 2017 or at the Ionian Fault system (Polonia et al, 2011;Scarfì et al, 2018) (Figure 2). An earlier proposition that the STEP fault follows the Malta Escarpment, a 3-km-high feature offshore E Sicily (Argnani & Bonazzi, 2005) formed during the Tethyan rifting history of the Ionian Sea (Frizon de Lamotte et al, 2011;Gallais et al, 2011), seems unlikely given the absence of tectonic deformation along the central to southern Malta Escarpment since the Messinian, on the basis of high-resolution seismic profiles shot across the escarpment (Gutscher et al, 2016).…”
Section: Tectonic History Of the Study Regionmentioning
confidence: 99%
“…In both cases wide-angle seismic studies have concluded that the downgoing lithosphere is most likely oceanic in nature and of Jurassic age (Sallarès et al, 2011;Dellong et al, 2018). Both subduction systems are characterized by extremely wide (~200 km downdip direction) accretionary wedge complexes, with very shallow surface angles and thus narrow tapers (Dellong et al, 2018;Gallais et al, 2012;Gutscher et al, 2002Gutscher et al, , 2009Gutscher et al, , 2012Gutscher et al, 2017). There is a broad consensus that apart from their large-scale morphotectonic similarities, both subductions formed through rollback of narrow slabs over the past 5-10 million yr (Chertova et al, 2014;Faccenna et al, 2004;Gutscher et al, 2002;Gutscher et al, 2017;Palano et al, 2017;van Hinsbergen et al, 2014).…”
Section: Narrow Curved Subduction Zones and Deep Slab Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Tectonics (e.g., Chaumillon & Mascle, 1995, 1997Minelli & Faccenna, 2010;Polonia et al, 2016) dependent upon convergence parameters, the nature and depth of the décollement levels, and the structure of the subducting plate and backstop (e.g., Bortoluzzi et al, 2017;Chaumillon et al, 1996;Gutscher et al, 2017;Reston, Fruehn, et al, 2002;. To the south, the structure of the African margin of the Ionian Basin is complex and may be delimited by the Eastern Sicily/Malta and Cyrenaica segments, with the offshore Sirte Basin in between.…”
Section: 1029/2018tc005472mentioning
confidence: 99%